“It seems so much the truth it is the truth”:: Persuasive Testimony in Alice Munro’s “A Wilderness Station” - Duncan, Isla (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2003)
Alice Munro's epistolary narrative "A Wilderness Station," like all narratives, contains a subtext to be decoded, in which two or more readers (both Munro's readers and the fictional addressees) are addressed in different ways within the same text. The reader is invited to reappraise various official versions of a local history through the act of decoding the message in the letters. While critics like Ildiko de Papp Carrington read disingenuousness in the "letters" of Annie McKillop—indeed, see the subtext as suggestive of sinister motives and sexual crimes—a careful reading of Munro's characterization suggests the character's honesty. The distortions are those of social convention, in which the official version of history seems to be given precedence; it is these that are to be viewed with suspicion, rather than the character's motives.